العوامل المحددة للرضا الوظيفي لدى العاملين بالمؤسسة الصناعية الجزائرية (دراسة حالة وحدة العصير والمصبرات نقاوس- باتنة-) - برو, هشام (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى قياس مدى الرضا عن مجموعة من العوامل التي تؤثر في بيئة العمل في المؤسسة الصناعية الجزائرية، وإبراز أكثر هذه العوامل تأثيراً وتحقيقاً للرضا الوظيفي،ولهذا الغرض فقد استخدم الباحث استبيان لجمع المعلومات تم توزيعه على عينة مكونة من 132 مرؤوس مباشر، كما استخدم كذلك المنهج الوصفي لوصف الظاهرة المراد دراستها، وأظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية بين استجابات أفراد عينة الدراسة حول الرضا الوظيفي لدى المرؤوسين المباشرين تعزى إلى المتغيرات الشخصية والديمغرافية ( الجنس، العمر، المؤهل العلمي، مدة الخدمة في المؤسسة، مدة العمل مع الرئيس المباشر الحالي، التخصص) بالمؤسسة محل الدراسة. This study aims to measure the extent of satisfaction with a group of factors that affect the work environment in the Algerian industrial establishment, highlighting the most influential factors and achieving job satisfaction, and for this purpose the researcher used a questionnaire to collect information that was distributed to a sample of 132 direct subordinates. As well as the descriptive approach to describe the phenomenon to be studied, and the results of the study showed that there are statistically significant differences between the responses of the study sample individuals about the job satisfaction of direct subordinates due to the personal and demographic variables (gender, age, academic qualification, duration of service in the institution, period with the current direct boss , Specialization) of the institution under study.
Factors determining job satisfaction among employees of the Algerian industrial establishment (case study of the unit of juice and canned food - Ngaous - Batna-)
مقال
Keywords: الرضا الوظيفي؛عوامل الرضا الوظيفي؛ المؤسسة الصناعية؛ العاملين.